Developing Discovery Learning Worksheet to Foster Junior High School Students’ Mathematical Literacy - Vita Istihapsari; Y. L. Sukestiyarno; Hardi Suyitno; Rochmad Rochmad (International Conference on Science, Education, and Technology, 2022)
This study aims to develop student worksheet for junior high school students in the setting of discovery learning and find out its validity and practicality. The developed worksheet is expected to be valid and practical to foster the students’ mathematical literacy. We used the framework of analysis, design, development, implementation, and evaluation (ADDIE) to develop the worksheet. During the development, we involved experts in school mathematics to review the content, experts in learning media to review the worksheet quality as a form of media, and 34 eight grade junior high school students in Yogyakarta to try out the worksheet. The material used in the worksheet is circle. During the validation process, we used the check list instrument, while in the try out process, we used questionnaire. This study successfully produced a valid and practical worksheet to foster the students’ mathematical literacy. Experts provide score of 151.5 (very good) in substantial aspect and score of 149 (very good) in media quality aspect. Moreover, the average score of students’ response towards the developed worksheet is 125.6 (good), which indicates that the worksheet is practical.